ASSESSMENT OF EDENTULISM AMONG OUTPATIENTS- AN INSTITUTIONAL STUDY - Sharma M, Neha; L. , Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
Background: The total rate of edentulism is said to be increasing in developing countries, and this has been attributed mainly to the high prevalence of periodontal diseases and caries. Several reports have shown that the prevalence of edentulism is higher in males than females. Aim: The aim of this study is to assess the edentulism based on ACP PDI classification among 65-74-year-old patients visiting a private dental hospital in Chennai Materials and methods: This was a comparative, descriptive study done during April-June, 2020, where all the data of the patients who reported to the dental clinics in Saveetha Dental College, SIMATS, Chennai, India, was obtained from the Department of Public Health Dentistry. Patient records were reviewed and analysed between June 2019 and March 2020. Data was collected and tabulated. The collected data was further analysed , recorded in Microsoft Excel software, and subjected to a chi-square test for statistical analysis using IBM SPSS software. Results: The total sample size of the current study was 1,244 cases. A male predilection was seen, with males making up 68% of the study population. The most common age group that was observed was 65-69 years, with 66%. The most commonly seen ACP PDI classification was Class I with 70%. On doing the Chi square test, it was found that among the males, Class I and Class II edentulousness was more prevalent, and among the females, Class III and Class IV edentulousness was found to be more prevalent. But it was found to be statistically insignificant (p value > 0.05) Conclusion: The study revealed that the Class I ACP PDI classification was more common than other classes. There was no significant association between edentulousness and gender and also between edentulousness and age among the outpatients. Awareness should be created among the public about the factors related to tooth loss and also about the treatment options available to treat the edentulous state.